2023
DOI: 10.7759/cureus.45353
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Liquid-Based Cytology and Conventional Smears in Fine-Needle Aspirates of Thyroid Lesions

Malti K Maurya,
Rita Yadav,
Madhu Kumar
et al.

Abstract: Background Palpable nodules in the thyroid are present in 4-7% of the general population. Fine-needle aspiration cytology is a safe and cost-effective method of choice for evaluating thyroid nodules. Aspirated samples can be manually spread directly onto the slide and stained in the conventional smear method. The liquid-cased cytology method has been recently introduced, which is an automated machine-based method, yielding a single slide with a clean background and greater preservation of cells and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…It gives an advantage to a clean background for the monolayered cells with well-preserved morphology and consumes less screening time. Liquid-based cytology is widely used in gynecological smears nowadays; however, a few studies have been reported in the literature for the interpretation of thyroid nodules [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It gives an advantage to a clean background for the monolayered cells with well-preserved morphology and consumes less screening time. Liquid-based cytology is widely used in gynecological smears nowadays; however, a few studies have been reported in the literature for the interpretation of thyroid nodules [28].…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies concluded that liquid-based cytology serves as a useful adjunct diagnostic method, and its combination with conventional smears has been shown to reduce unnecessary thyroidectomies due to the good identification of malignant and suspicious thyroid lesions [28,29]. However, a recently published meta-analysis study by Kang et al in 2024 [30] concluded that the diagnostic accuracy of FNAC in thyroid nodules did not significantly differ among conventional and/or liquid-based cytology, but comparing two kits (ThinPrep and SurePath) revealed a significant difference, suggesting that SurePath kits might be more accurate.…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized for its simplicity and convenience [8]. Furthermore, it is relatively safe, repeatable, and low risk [6,7,9,10]. However, CS can report variable results, depending on the uneven thyroid tissue samples or cytopathologist's experience [8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…However, CS can report variable results, depending on the uneven thyroid tissue samples or cytopathologist's experience [8,10,11]. Artifacts may also arise during the drying of specimens, and results can vary by technician [9]. In addition, the presence of fibrosis and cystic lesions can result in poor cellularity [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation